2023
DOI: 10.1101/2023.10.16.23297086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photodynamic therapy is a safe and feasible adjunct to percutaneous drainage of deep tissue abscesses: Results of a first in humans Phase 1 clinical trial

Timothy M. Baran,
David A. Bass,
Laurie Christensen
et al.

Abstract: Background: Standard of care for abscess management includes image-guided percutaneous drainage and antibiotics. However, cure rates vary between patients and there is growing concern for antibiotic-resistant bacteria. Photodynamic therapy (PDT), which utilizes light-activated dyes to generate cytotoxic reactive species, could complement the standard of care by sterilizing the abscess at time of drainage. Purpose: The goal of this study was to perform a first in humans Phase 1 clinical study evaluating safety … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Based on encouraging pre- clinical results showing that PDT with methylene blue (MB) is efficacious against multiple bacteria typically found in abscesses 6,11,12 , we initiated a Phase 1 clinical trial investigating the safety and feasibility of MB-PDT at the time of abscess drainage (ClinicalTrials.gov identifier: NCT02240498). We found that MB-PDT was safe, with no study-related adverse events observed 8 . Additionally, preliminary analysis suggests that symptom resolution was faster and drainage catheter discharge was reduced in subjects receiving higher fluence.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Based on encouraging pre- clinical results showing that PDT with methylene blue (MB) is efficacious against multiple bacteria typically found in abscesses 6,11,12 , we initiated a Phase 1 clinical trial investigating the safety and feasibility of MB-PDT at the time of abscess drainage (ClinicalTrials.gov identifier: NCT02240498). We found that MB-PDT was safe, with no study-related adverse events observed 8 . Additionally, preliminary analysis suggests that symptom resolution was faster and drainage catheter discharge was reduced in subjects receiving higher fluence.…”
Section: Introductionmentioning
confidence: 60%
“…In all cases, the goal was to determine the delivered optical power (threshold optical power) and lipid emulsion concentration necessary to achieve a desired fluence rate of 4 mW/cm 2 or 20 mW/cm 2 in 95% of the abscess wall, while limiting the portion of the wall that receives a fluence rate of 400 mW/cm 2 to less than 5%. The 4 mw/cm 2 target is based upon an efficacious pre- clinical condition 6,12 , while the 20 mW/cm 2 target is the target fluence rate used clinically 8 to account for the more demanding in vivo scenario. The final treatment plan was determined by the lipid emulsion concentration that minimized the threshold optical power.…”
Section: Methodsmentioning
confidence: 99%
“…Spectroscopy data were collected from subjects enrolled in a Phase 1 clinical trial examining the safety and feasibility of methylene blue photodynamic therapy performed at the time of percutaneous abscess drainage (ClinicalTrials.gov Identifier: NCT02240498). The primary results of this clinical trial are reported separately 8 . Of the 18 subjects treated in this trial, optical spectroscopy data were collected from the final 13 subjects as described below.…”
Section: Participants and Regulatory Approvalmentioning
confidence: 99%
“…All subjects first had their abscess drained using standard of care image-guided percutaneous drainage, as described in the main trial report 8 . This procedure utilized CT guidance for 16 subjects and ultrasound guidance for 2 subjects.…”
Section: Clinical Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation